Lower Arch Dimensions in Children with Anterior Open Bite and Normal Vertical Overbite: A Cross-sectional Study (2019)
Aim: Dental arch is a dynamic structure and its size depends on genetic and environmental factors. The aim of this study was to determine lower arch dimensions in children between 8 and 16 years with anterior open bite (AOB) and normal vertical overbite (NVO). Materials and Methods: A cross-sectional study was performed in 132 individuals with AOB and 132 with NVO between 8 and 16 years selected from public schools. Intercanine width, arch length, intermolar and interpremolar distances, and arch perimeter of the lower arch were measured in previously digitalized models using the GOM inspection program and an optical three-dimensional scanner. Results: Individuals with NVO presented smaller lower arch size with statistical differences in intercanine (P = 0.024, 95% confidence interval [CI]: 0.01, 0.02) and intermolar (P = 0.000, 95% CI: −1.76, −0.53) width and nonsignificant differences in the arch perimeter (P = 0.239, 95% CI: −1.57, 0.39) according to Mann–Whitney U-test. Conclusion: Individuals between 8 and 16 years of age with NVO showed smaller lower dental arch than individuals with AOB in most dimensions